Long-acting injectable aripiprazole in pregnant women with schizophrenia: a case-series report. (January 2021) - Fernández-Abascal, Blanca; Recio-Barbero, Maria; Sáenz-Herrero, Margarita; Segarra, Rafael
Antipsychotic long-acting formulations (LAI-AP) have emerged as a new therapeutic choice to treat patients presenting a severe mental disorder. Despite that, to date, there is a lack of safety data and studies regarding the use of LAI-AP formulations in pregnant women. Here we present the first six-case series of pregnant women with schizophrenia treated with aripiprazole-LAI reported in the literature. All patients remained psychopathologically stable through pregnancy and the postpartum period, and all of them were in treatment with aripiprazole-LAI. To date, all infants remain healthy with normal developmental milestones, without the presence of congenital malformations or adverse effects. Lack of information on safety data regarding the use of new antipsychotic formulations remains important in treating women with mental illness who desire to become pregnant. Further studies in this clinical population with a larger number of patients included remains necessary.